EFFECT OF RASAPRAVICHARANA CIKITSA (TASTE SPECIFIC DRUG THERAPY) IN KAPHA DOMINANCE OF TAMAKA SWASA (ASTHMA) - A CASE SERIES (International Journal of Ayurveda and Pharma Research, 2018)
Rasapravicharana cikitsa is the administration of drugs in accordance with the Rasam (taste) after assessing the Doshic imbalance in diseases. The basic approach of Ayurveda is to normalize the Doshas in aggravated or depleted conditions occurred in the manifestation of disease. The objective of the study was to assess the effect of Rasapravicharana cikitsa (taste specific drug therapy) in aggravated Kapha dosha of Kapha dominant Tamaka swasa (asthma). The study was conducted on 10 patients between the age group 16 to 70 yrs of both the sexes. The patients were administered with Katu (pungent) rasa drug ie, powder of the dried fruit of Maricham (Piper nigrum Linn) at the dose of 500 mg, Tikta (bitter) rasa drug i.e., dried Vasa leaf powder (Adhatoda vasica Nees) at the dose of 3gm, and Kashaya (astringent) rasa drug i.e., powder of the dried fruit pericarp of Haritaki (Terminalia chebula (Gaertn.) Retz.) at the dose of 3gm, 8 AM and 8 PM after food daily in luke warm water respectively for a period of two weeks each.The Katu rasa drug administered for 14 days produced highly significant reduction in dyspnoea, cough bout frequency, wheeze, expectoration of sputum and quantity of sputum, and significant improvement in PEFRate. But no significant improvement was observed in PEF%. The administration of Tikta rasa drug in the next 14 days resulted in highly significant reduction in cough bout frequency and expectoration of sputum and significant reduction in dyspnoea. The reduction was maintained in other signs and symptoms. The Kashaya rasa drug used in the last 14 days significantly improved PEFRate. Reduction in other signs and symptoms was maintained. The management according to Rasapravicharana cikitsa has a significant role in the pacification of Doshas involved in the manifestation of diseases.